ChemInform Abstract: Structure, Photochemistry and Applications of Metal‐Doped Polyoxotitanium Alkoxide Cages. Issue 51 (23rd December 2014) - Matthews, Peter D.; King, Timothy C.; Wright, Dominic S.
Abstract Review: 110 refs.